Relationship of Traffic Noise with High Blood Pressure to Pedicab Drivers Around Purabaya Bus Station Surabaya - Shita Addina; Soedjajadi Keman (JURNAL KESEHATAN LINGKUNGAN, 2015)
Abstract: The existence of bus  station  can  make  some problems, one  of which  is the traffic noise. Traffic noise  can induce an increased blood pressure. Therefore, the purpose of this study was to analyzed the relationship  between level of traffic noise  and increased blood  pressure in pedicab drivers around Purabaya bus station. The study was carried out using  by cross sectional method. Measurement of traffic noise  was carried out around  Purabaya bus station Surabaya with Sound Level Meter. Measurement of blood  pressure with sphygmomanometer. Sampling method used by simple random  sampling with 22 respondents respectively and  then  total of respondents are 44 respondents. The  result of study  indicated there  was  a relationship  between the level traffic noise  with increased blood  pressure (hypertension) (p = 0.034). Another factor related to blood  pressure was descendants of the family history (p = 0.002). It was concluded that traffic noise  related with increased blood pressure in pedicab drivers. Suggested for the next researcher doing  the measurement noise  more than a day to get the actual average noise  level. In addition, other factors related to the blood pressure should examined to get main factor of hypertension.Keywords: traffic noise, blood  pressure, pedicab drivers